Reduced-impact logging in Borneo to minimize carbon emissions and impacts on sensitive habitats while maintaining timber yields - Griscom, Bronson W.; Ellis, Peter W.; Burivalova, Zuzana; Halperin, James; Marthinus, Delon; Runting, Rebecca K.; Ruslandi; Shoch, David; Putz, Francis E. (Forest ecology and management, 2019)
•RIL-C practices reduce emissions by 33% to 46% by improving logging efficiency.•Sensitive habitats can be protected from logging without reducing timber yields.•These offer large outcomes for Paris Climate Agreement and Aichi targets. We define two implementation levels for reduced-impact logging for climate mitigation (RIL-C) practices for felling, skidding, and hauling in dipterocarp forest concessions of East and North Kalimantan. Each implementation level reduces logging emissions by a consistent proportion below the business-as-usual emissions baseline, which varies with harvest intensity. Level 1 reflects the best recorded emissions performance for each type of practice. Level 2 is more ambitious but feasible based on workshop feedback from concession managers and forestry experts, and confirmed by a recent demonstration. At Level 1 emissions can be reduced by 33%, avoiding emissions of 64.9 ± 22.2 MgCO2 per ha harvested, on average. At Level 2 emissions can be reduced by 46%, avoiding 88.6 ± 22.7 MgCO2 ha−1. The greatest emissions reductions derive from (i) not felling trees that will be left in the forest due to commercial defects, and (ii) use of long-line cable winching to avoid bulldozer impacts. We also quantify the potential to avoid logging steep slopes and riparian habitats, while holding to our RIL-C accounting assumption that timber yields are maintained to avoid problems of leakage and product substitution. Logging damage to riparian areas <50 m from perennial streams could be avoided by re-locating harvests to less sensitive areas that currently are not accessed due to lack of spatial planning. In all but the steepest concessions, all slopes >40% could similarly be avoided. The combined areas of these sensitive habitats (steep slopes and riparian buffers) represented 16% of each cutting block on average. Implementation of RIL-C practices would deliver 8% (Level 1) and 11% (Level 2) of Indonesia’s pledged reductions to their forest reference emissions level as a nationally determined contribution to the Paris Climate Agreement. In concert with RIL-C practices, 30% of logging concession areas could be permanently protected from logging and conversion to minimize impacts on biodiversity, soils, and water quality, thereby expanding Indonesia’s protected areas by one third and achieving 93% of Indonesia’s Aichi Target 11 (the effective conservation of at least 17% of lands). Both these Paris Climate Agreement and Aichi outcomes could be delivered with no reductions in timber yields and substantial improvements in worker safety and sustainability of the natural forest timber sector.